THE EFFECT OF PRICE ON CUSTOMER LOYALTY THROUGH THE PERCEPTION OF PRODUCT SUSTAINABILITY - Muhammad Mathori; Diah Retno Wulandaru (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study aims to examine the influence of price on customer loyalty through the perception of product sustainability in the bottled mineral water industry in Yogyakarta. The price factor is crucial in shaping the perception of value and sustainability, which further influences consumer loyalty. Based on stimulus-reaction (S-O-R) theory, price serves as a stimulus that influences customers' internal perceptions of sustainability, thereby motivating them to remain loyal to a particular brand. The study used a quantitative methodology with data collected through questionnaires from mineral water customers in the region. The results of the analysis show that price has a positive and significant effect on the perception of product sustainability and customer loyalty. In addition, the perception of sustainability acts as a mediating variable that strengthens the relationship between price and loyalty. These findings underscore the importance of pricing strategies supported by transparent communication about sustainability to increase customer loyalty. Nonetheless, the results also show that the perception of sustainability does not necessarily guarantee loyalty if other factors such as quality and price perception are not supportive. The limitations of the study include contextual factors and moderation variables that have not been fully explored. Future research is suggested to review other variables, use a longitudinal approach, and engage a variety of industries to strengthen the generalization and applicability of results. These findings contribute to businesses in designing effective and sustainable sustainability-based marketing strategies.